Integrating Empathy into Classroom Assessment Design (Journal of School Administration Research and Development, 2025)
Traditional assessment design focuses on outcomes and often disregards how students perceive their abilities, process emotions, or self-express. This indifference can undermine assessment outcomes and evaluation reliability (Hattie, 2023; Nilson, 2023; Reibel 2022). This paper introduces empathetic assessment design (EAD), a framework that reframes assessment as an event to simultaneously understand the student while evaluating their abilities to provide more precise grading and improved support. EAD integrates cognitive (self-evaluation), emotional (appraisal of emotional reactions and mindsets), and relational (self-expression) dimensions, enriching assessments with experiential insights. The information resulting from the EAD design provides context for outcomes and helps teachers assess the adequacy of student thinking, affective reactions, and needs. Despite concerns about workload and rigor, EAD builds on established theories—Bandura’s social cognitive theory (1997), Joe Feldman’s Grading for Equity (2018), and funds of knowledge and culturally responsive pedagogy (Ladson-Billings, 1995, 2021; Moll, 2015, 2019)—to create more insightful assessments. EAD complements equitable grading practices, gathering students’ real-time experiential information (Blum, 2020; Colby, 2019; Clark & Talbert, 2023; Feldman, 2018). While experts (Hattie, 2023, 2018; Schimmer, 2016; Wiliam, 2011) advocate for self-assessment and reflection, they often position these outside the assessment itself. But EAD embeds them within assessments, capturing in-the-moment insights to make evaluation more meaningful and illuminating.